Au sub(36)(SPh) sub(24) Nanomolecules: X-ray Crystal Structure, Optical Spectroscopy, Electrochemistry, and Theoretical Analysis - Nimmala, Praneeth Reddy; Knoppe, Stefan; Jupally, Vijay Reddy; Delcamp, Jared H; Aikens, Christine M; Dass, Amala (The journal of physical chemistry. B, 2014)
The physicochemical properties of gold:thiolate nanomolecules depend on their crystal structure and the capping ligands. The effects of protecting ligands on the crystal structure of the nanomolecules are of high interest in this area of research. Here we report the crystal structure of an all aromatic thiophenolate-capped Au sub(36)(SPh) sub(24) nanomolecule, which has a face-centered cubic (fcc) core similar to other nanomolecules such as Au sub(36)(SPh-tBu) sub(24) and Au sub(36)(SC sub(5)H sub(9)) sub(24) with the same number of gold atoms and ligands. The results support the idea that a stable core remains intact even when the capping ligand is varied. We also correct our earlier assignment of "Au sub(36)(SPh) sub(23)" which was determined based on MALDI mass spectrometry which is more prone to fragmentation than ESI mass spectrometry. We show that ESI mass spectrometry gives the correct assignment of Au sub(36)(SPh) sub(24), supporting the X-ray crystal structure. The electronic structure of the title compound was computed at different levels of theory (PBE, LDA, and LB94) using the coordinates extracted from the single crystal X-ray diffraction data. The optical and electrochemical properties were determined from experimental data using UV-vis spectroscopy, cyclic voltammetry, and differential pulse voltammetry. Au sub(36)(SPh) sub(24) shows a broad electrochemical gap near 2 V, a desirable optical gap of similar to 1.75 eV for dye-sensitized solar cell applications, as well as appropriately positioned electrochemical potentials for many electrocatalytic reactions.